Assessment of Design and Retrofitting Solutions on the Progressive Collapse of Hongqi Bridge - Amir Seyed Khoei; Reza Akbari; Shahrokh Maalek; Alireza Gharighoran (Shock and Vibration)
In 2009, the Hongqi Bridge, a multispan reinforced concrete bridge located in Zhuzhou, Hunan Province, China, collapsed progressively in the form of domino, due to extreme effect of deck to pier, during demolition process of the bridge. In this study, progressive collapse of Hongqi Bridge was investigated using nonlinear dynamic analysis in the Applied Element Method, which has been proven as one of the best methods that can follow the collapse behavior of structures. Good agreements were obtained between numerical results and field observations as well as previously reported results. After verifying the bridge collapse procedure, the effects of different alternatives for superstructure and substructure systems on the progressive collapse procedure were investigated. In addition, application of restrainers at the connection of deck to abutment was studied as an effective solution in order to prevent collapse propagation and to minimize associated damages. The results of the study showed that all chosen methods and factors could be helpful and effective in the procedure of collapse propagation for this kind of bridge.